Poly(C)-binding proteins as transcriptional regulators of gene expression - Choi, Hack Sun; Hwang, Cheol Kyu; Song, Kyu Young; Law, Ping-Yee; Wei, Li-Na; Loh, Horace H. (Biochemical and biophysical research communications, 2009)
Poly(C)-binding proteins (PCBPs) are generally known as RNA-binding proteins that interact in a sequence-specific fashion with single-stranded poly(C). They can be divided into two groups: hnRNP K and PCBP1-4. These proteins are involved mainly in various posttranscriptional regulations (e.g., mRNA stabilization or translational activation/silencing). In this review, we summarize and discuss how PCBPs act as transcriptional regulators by binding to specific elements in gene promoters that interact with the RNA polymerase II transcription machinery. Transcriptional regulation of PCBPs might itself be regulated by their localization within the cell. For example, activation by p21-activated kinase 1 induces increased nuclear retention of PCBP1, as well as increased promoter activity. PCBPs can function as a signal-dependent and coordinated regulator of transcription in eukaryotic cells. We address the molecular mechanisms by which PCBPs binding to single- and double-stranded DNA mediates gene expression.